Parenting high achieving boys in poverty – critiquing 'active cultivation' as an explanation for 'beating the odds' in the early years. Issue 2 (3rd April 2021) - Simpson, Donald
ABSTRACT: A powerful discursive formation claims 'bad parenting' amongst the poor predisposes their children to educational underachievement. A small number of children in poverty succeeding within early education potentially undermines this construction of 'parent blame'. This requires an explanation which perpetuates the dominant discourse about deficiencies amongst the poor, one which suggests 'good parenting' is resource free, context-neutral and achievable once parents in poverty change their ways. This article argues the concept of active cultivation has gained traction because it offers this with its focus on 'the proximal' in child development. But, drawing on data from parents in poverty whose children 'beat the odds' in early education, it is argued active cultivation has limitations as an explanation, downplays the importance of resources connected to socio-economic status in parenting, and is part of a wider trope justifying political direction.